Chromatographic Fingerprinting of Sarasvata Churna−an Ayurvedic Polyherbal Formulation for Epilepsy - Rahul Kaushik, Jainendra Jain, Avijit Mazumder (Journal of Applied Pharmaceutical Science, 2018)
Sarasvata churna is an Ayurvedic formulation prescribed for Epilepsy and other brain-related disorders. The objective of this study is to explore bioactive principles present in Sarasvata churna using GCMS and HPTLC techniques and establishing their correlation in Epilepsy treatment. The volatile oil obtained by hydrodistillation was used for the GCMS analysis and methanolic extracts were used for HPTLC studies. HPTLC fingerprints for the formulation and method for simultaneous qualitative analysis of biomarkers in the formulation was developed using HPTLC. The GCMS report shows the presence of α-Pinene, Propanal, 2-Caren-10-al, 3-Caren-10-al, Caryophyllene, Epiglobulol, Asarones, α-selinene, α-sesquiphellandrene, o-cymene, copaene etc. HPTLC fingerprints for methanolic extracts of Sarasvata churna was established with good separation and resolution in solvent system Toluene:Ethylacetate: Methanol (7.5:2.5:0.5 v/v/v). The HPTLC method for simultaneous analysis of marker compounds in the formulation was developed in solvent system Ethylacetate:Glycial acetic acid:Toluene:Water (4:1:1:0.5 v/v/v/v) with Rf 0.77 for Piperine, 0.07 for Bacosides and Rf 0.57 for Withnolides in the reference compounds and methanolic extracts of Sarasvata churna. Chromatographic patterns of reference compounds were easily detectable in the tracks of Sarasvata churna methanolic extracts. The chromatographic standards obtained from this study will help in chemical standardization of Sarasvata churna and enhance the use Sarasvata churna for management of Epilepsy.
Keywords: Sarasvata churna, Polyherbal formulation, Ayurvedic, HPTLC, GC-MS, Epilepsy.